The Present and Future of Szigetvár Spa – An Economic Analysis of Geothermal Energy Investment - Judit Pálné Schreiner (DETUROPE)
In Hungary, geothermal energy has proved to be an economical source of energy for direct use. It highlights the pros and cons of including renewable energy in the power generation mix of Hungary, and the pros and cons of local application. This paper looks at the operation of Szigetvár Spa from both economic and social aspects. In this study, qualitative analysis is used for the basic economic and social introduction of the Spa, and then real options, based on quantitative methods, are described to identify the long-term financial consequences of the project. In 1966, thermal water was found in Szigetvár. In 1997, this thermal water was certified as medicinal water. The wellhead temperature of Szigetvár thermal water is 62°C in the 790 metres deep thermal well. It is used as so-called domestic hot water in the Szent István housing estate and in Szigetvár Spa. One of the problems with the project is that it is based on single stage thermal water utilization, another problem is that the waste water is too hot. This can be solved by exploiting the heat energy of thermal water more intensively. This way, maximum benefits can be gained from geothermal energy with minimum use of energy. Static and dynamic investment analyses were carried out to examine the spa from a financial aspect. The methods used include static payback period, average rate of return, levelized cost of electricity, net present value, profitability index, dynamic payback period, internal rate of return and real options. By pricing geothermal technology, it is possible to identify the strategic value of flexibility, to quantify what was previously left unquantified, and thus to show that geothermal investments are profitable not only from a social but also from a financial aspect as well.